ANALISIS PERBANDINGAN SISTEM PENDIDIKAN DI INDONESIA, UNI EMIRAT ARAB, DAN SINGAPURA DALAM INOVASI PEMBELAJARAN SAINS - Marsila, Sinta; Sosri, Lexa; Rahayu, Putri Wiji; Vreticia, Enjel; Koto, Irwan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT Science education markedly improves a nation's competitiveness within the framework of globalization. This study seeks to analyze the differences in science education systems in Indonesia, the United Arab Emirates (UAE), and Singapore, focusing on policy, curriculum, pedagogical methods, and technological integration in education. The research is a descriptive qualitative applying comparative study method. Data was collected through literature review and document analysis from several relevant and reliable sources. The results demonstrate that the three nations utilize significantly different approaches to science education. Indonesia persists in facing challenges regarding the equitable distribution of science laboratory facilities, the training of science instructors, and the integration of technology in scientific education. The UAE has established an education system based on science, technology, and mathematics, employing artificial intelligence-enhanced educational technology and virtual laboratories. Singapore specializes in experiential learning, supported by sophisticated infrastructure and continuous professional development. The success factors for science education are the integration of technology, the improvement of science teacher skills, and the establishment of regulations that support project-based learning. Indonesia can improve the quality of science education by adopting successful strategies from the UAE and Singapore, such as strengthening the function of science laboratories, increasing technological access in schools, and establishing systematic and sustainable training for science instructors. This study's recommendations aim to assist policymakers in enhancing the quality of science education in Indonesia. ABSTRAK Pendidikan sains memainkan peran penting untuk meningkatkan daya saing suatu negara di era globalisasi. Karena pentingnya pendidikan sains, tujuan penelitian ini adalah untuk menganalisis perbedaan sistem pendidikan sains di Indonesia, Uni Emirat Arab (UEA), dan Singapura, yang difokuskan pada aspek kebijakan, kurikulum, metode pembelajaran, serta integrasi teknologi dalam pendidikan. Penelitian ini adalah deskriptif kualitatif dengan metode studi komparatif. Data dikumpulkan melalui kajian literatur, dan analisis dokumen dari berbagai sumber yang valid dan terpercaya. Hasil penelitian menyatakan bahwa ketiga negara mengimplementasikan pendekatan yang relatip berbeda dalam pendidikan sains. Indonesia menghadapi tantangan dalam pemerataan infrastruktur laboratorium, pelatihan guru, dan integrasi teknologi dalam pembelajaran sain. UEA telah mengadopsi pendidikan berbasis STEM dan teknologi berbasis kecerdasan buatan dan laboratorium virtual. Sedangkan, Singapura unggul dalam pembelajaran berbasis eksperimen, didukung oleh infrastruktur yang lengkap dan pelatihan guru yang berkelanjutan. Faktor-faktor utama keberhasilan pendidikan sains meliputi integrasi teknologi dalam pendidikan, peningkatan kompetensi guru sains, serta kebijakan yang mendukung project-based learning. Indonesia dapat meningkatkan kualitas pendidikan sains dengan mengadopsi praktik baik dalam pembelajaran dari UEA dan Singapura, seperti penguatan fungsi laboratorium sains, peningkatan akses teknologi oleh sekolah-sekolah, dan pelatihan guru sains yang sistematis dan berkelanjutan. Rekomendasi dari penelitian ini diharapkan dapat memberikan wawasan bagi pengambil kebijakan dalam meningkatkan mutu pendidikan sains di Indonesia.